Space‐Confined Growth of 2D InI Showing High Sensitivity in Photodetection - Abdulsalam Aji Suleiman; Pu Huang; Bao Jin; Jizhou Jiang; Xiuwen Zhang; Xing Zhou; Tianyou Zhai (Advanced Electronic Materials, 2020)
Abstract Layered InI has a great potential in optoelectronic applications due to its direct wide tunable bandgap. However, there is no single report about its 2D synthesis. Here, the growth of high‐quality and ultrathin InI flake (as thin as 8 nm) is reported via space‐confined physical vapor deposition. Impressively, an InI flake‐based photodetector exhibits an ultralow off‐state current of ≈4.2 × 10−12 A, high on/off photocurrent ratio of 104, excellent detectivity of 4.2 × 1012 Jones, a high‐speed response time of 10 ms, as well as excellent effective quantum efficiency of 1600%, suggesting its promising applications in optoelectronics.